Community owned green gym of a village in Maharashtra, India: a case study of community empowerment - Devyani Wanjari; Radhika Sharma; Pravin Bhusari; Chanda Bhondwe; Abhishek V. Raut; Subodh S. Gupta; V.-CaN Collaboration Team (Discover Social Science and Health)
Abstract Community empowerment is the ultimate goal of any community engagement activity in public health. This article is about the experiments done and efforts taken by different stakeholders and organizations for making villagers prioritize their health problems, find probable solutions and mobilize them for their own health needs. This includes the Community Owned Clinic (Kiran Clinic) of the village, “Village Adoption Scheme” of the medical institute, Vitalizing Communities against Non-communicable diseases (V-CaN) project of the Department of Community Medicine of the Institute, etc. Various other factors like consistent community work by the social workers of the department for the health and wellbeing of the villagers, trust-based relationship with the medical institute, active participation of the Gram Panchayat of the village in central India and other village organizations like SHGs, sports club and enthusiasm of the villagers, etc. were the driving forces for the community participation. This case study is a good example of the process of community participation where the community takes part in decision making, while it also serves as a good example of engaging future doctors with the community to promote values and skills like empathy, communication, team work, etc. within them.